On necessary and sufficient conditions for the summability of a numerical series to imply its convergence - Davydov, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
On the basis of the concepts of (C) -point and (¯R, p)-point of a sequence of complex numbers introduced by the author and results established earlier, we formulate necessary and sufficient conditions for the summability of a number series by a positive Cesaro method or the Riesz method to imply the convergence of this series. We also present a sufficient condition for summability to imply the convergence of a subsequence of its partial sums.